Taurodeoxycholate Increases the Number of Myeloid-Derived Suppressor Cells That Ameliorate Sepsis in Mice - Chang, Sooghee; Kim, Youn-Hee; Kim, Young-Joo; Kim, Young-Woo; Moon, Sungyoon; Lee, Yong Yook; Jung, Jin Sun; Kim, Youngsoo; Jung, Hi-Eun; Kim, Tae-Joo; Cheong, Taek-Chin; Moon, Hye-Jung; et al. (Frontiers in Immunology, 2018)
Bile acids (BAs) control metabolism and inflammation by interacting with several receptors. Here, we report that intravenous infusion of taurodeoxycholate (TDCA) decreases serum pro-inflammatory cytokines, normalizes hypotension, protects against renal injury, and prolongs mouse survival during sepsis. TDCA increases the number of granulocytic myeloid-derived suppressor cells (MDSC-LT) distinctive from MDSCs obtained without TDCA treatment (MDSC-L) in the spleen of septic mice. FACS-sorted MDSC-LT cells suppress T-cell proliferation and confer protection against sepsis when adoptively transferred better than MDSC-L. Proteogenomic analysis indicated that TDCA controls chromatin silencing, alternative splicing, and translation of the immune proteome of MDSC-LT, which increases the expression of anti-inflammatory molecules such as oncostatin, lactoferrin and CD244. TDCA also decreases the expression of pro-inflammatory molecules such as neutrophil elastase. These findings suggest that TDCA globally edits the proteome to increase the number of MDSCLT cells and affect their immune-regulatory functions to resolve systemic inflammation during sepsis.